2016
DOI: 10.1002/jcu.22365
|View full text |Cite
|
Sign up to set email alerts
|

Sonographic measurements of the achilles tendon, plantar fascia, and heel fat pad are reliable: A test‐retest intra‐ and intertester study

Abstract: US is a reliable technique of measurement in the daily clinic, and one single measurement is sufficient. In research, we recommend that the same observer performs the US measurements, if one single scanning is preferred; if more researchers are involved, the average measurement of two US scans is recommended. © 2016 Wiley Periodicals, Inc. J Clin Ultrasound 44:480-486, 2016.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 25 publications
2
19
0
5
Order By: Relevance
“…In another study performed by Johannsen et al [11], conducted on 17 patients suffering from heel pain, they showed excellent interobserver reliability using the mean of two measurements (ICC 0.85 -0.95).…”
Section: Discussionmentioning
confidence: 93%
“…In another study performed by Johannsen et al [11], conducted on 17 patients suffering from heel pain, they showed excellent interobserver reliability using the mean of two measurements (ICC 0.85 -0.95).…”
Section: Discussionmentioning
confidence: 93%
“…Many other studies have used healthy volunteers which often make it easier to obtain good images because of the more marked boundaries compared to that of a sick tendon [2]. Others have only been shown pictures of images without obtaining them themselves and some have spent 6 minutes per obtained image [4,7].…”
Section: Discussionmentioning
confidence: 99%
“…The study was part of a randomized clinical trial evaluating the treatment of plantar fasciitis including intra-and inter-observer reliability among senior specialists [2].…”
Section: Methodsmentioning
confidence: 99%
“…The patients were lying prone face down with their feet hanging loose using the same US technique proven with high reliability for examining the plantar fascia, the plantar fat pad, and the Achilles tendon by the same rheumatologist (FJ). 18 All feet were examined for hypo-and hyperechoic changes within the fascia and with color Doppler, and the thickness of the central band of the plantar fascia was measured. To ensure it was the central band, the fascia was followed from the forefoot and back to the insertion on the calcaneus (Figure 1).…”
Section: Methodsmentioning
confidence: 99%